A combined cooling, heating and power system with energy storage of waste heat to hydrogen. (5th May 2023) - Ge, Yi; Han, Jitian; Zhu, Xiaoxuan; Zhu, Wanchao; Yang, Jinwen
Highlights: An improved CCHP system is proposed with waste heat recovery and energy storage. The system exergy efficiencies in three modes are higher than the reference system. The system performances in three modes are analyzed under off-design conditions. Chemical reactions primarily account for the system exergy destructions. Optimal conditions and performances are determined by NSGA-II and decision methods. Abstract: To improve the recovery of waste heat, a natural-gas based combined cooling, heating and power (CCHP) system with waste-heat to hydrogen as energy storage is proposed. In the novel system, the steam reforming of methanol (SRM) is applied in between the internal combustion engine (ICE) and absorption chiller, and integrated with a hydrogen tank and proton exchange membrane fuel cell (PEMFC) for energy storage. The mathematical model is developed to identify the thermodynamic performances of the system in three operation modes (normal, storage, supplemental) under design and off-design conditions, and multi-objective optimization is conducted to explore the optimal system performances. The results show that the overall exergy efficiencies of the three modes and reference system are 41.71 %, 46.34 %, 43.63 % and 40.51 % with given conditions, respectively. Except for ICE, the reactor accounts for 10.2% and 11.1 % exergy destruction ratio in M1 and M2 modes, while PEMFC accounts for 15% in M3 mode due to the chemical reactions. The parametric analysis demonstrates that increasing reaction temperature of SRM, methanol flow rate or working pressure of PEMFC can enhance the system exergy efficiencies for all modes. The optimal points determined by two decision methods are coincident and the energy and exergy efficiencies are 80.50 % and 43.00 %, which have increased by 0.36 % and 3.09 % than that under design conditions. The study constructs a promising scheme for realizing hydrogen storage by recovering the waste heat, and the results have verified the feasibility of the system and provided thermodynamic basis for further system configurations.